2007
DOI: 10.1007/s11270-007-9504-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Small- and Large-scale Ultrafiltration Systems for Organic Carbon and Metals in Freshwater at Low Concentration Factor

Abstract: Interdisciplinary studies on aquatic environments and cross-validation of laboratory vs. field results will likely increase the need for simultaneous use of large-and small-scale ultrafiltration systems. In this study, a comparison of two ultrafiltration systems differing in scale (PrepScale and PelliconXL, Millipore; membrane areas 0.54 m 2 and 0.005 m 2 , respectively), was made for the cut-offs 3 and 300 kDa. Large systems are useful for their high permeate throughput, while small systems are necessary when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
(22 reference statements)
1
11
0
Order By: Relevance
“…Stordal et al therefore suggested using CFs smaller than 10 for more consistent results in the partitioning of both Hg and DOC concentrations. Furthermore, Kottelat et al showed that increasing CFs resulted in the formation of large colloids in the retentate fraction of ultrafiltered waters, with possible consequences on element fractionation between colloids and true solution. In any case, our choice of CFs was actually dictated by the need to preserve a minimum sample volume for the subsequent chemical analysis of retentate fractions, especially for porewaters when the volume to ultrafilter was sometimes less than 100 mL (Supplemental Data, Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stordal et al therefore suggested using CFs smaller than 10 for more consistent results in the partitioning of both Hg and DOC concentrations. Furthermore, Kottelat et al showed that increasing CFs resulted in the formation of large colloids in the retentate fraction of ultrafiltered waters, with possible consequences on element fractionation between colloids and true solution. In any case, our choice of CFs was actually dictated by the need to preserve a minimum sample volume for the subsequent chemical analysis of retentate fractions, especially for porewaters when the volume to ultrafilter was sometimes less than 100 mL (Supplemental Data, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Tangential flow ultrafiltration was carried out using a Pellicon XL cartridge (regenerated cellulose, 3 kDa nominal cutoff). Before each use, the ultrafiltration membrane was thoroughly cleaned and preconditioned as described elsewhere . An ultrafiltration blank was performed before fractionation of each sample, using milliQ grade water to assess the background levels of THg and MMHg in the different laboratories (Supplemental Data, Table S2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its nature as a one step procedure, FlFFF/CFM can be coupled on-line between any sequential extraction unit and the ICP-OES system. The concept of the FlFFF/CFM is similar to that of the cross flow filtration generally used for colloid separation [26,27]. During cross flow matrix removal step, matrix free ions were filtered off through the membrane (1000) whereas the analyte-PEI complexes (25,000) retained in the FlFFF channel and traveled through the channel for ICP detection.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have shown that colloids are quite mobile in the aquatic system (Guo et al, 2001;Kottelat et al, 2008;Nowack and Bucheli, 2007). This revelation bring a number of question on use of redox-transform from U(VI) to an insoluble U(IV) phase as a mean of immobilising uranium from the water pathway.…”
Section: Introductionmentioning
confidence: 99%